Neurotensin inversely modulates maternal aggression - Gammie, Stephen C. (2008)
Neurotensin (NT) is a versatile neuropeptide involved in analgesia, hypothermia, and schizophrenia. Although NT is released from and acts upon brain regions involved in social behaviors, it has not been linked to a social behavior. We previously selected mice for high maternal aggression (maternal defense), an important social behavior that protects offspring, and found significantly lower NT expression in the CNS of highly protective females. Our current study directly tested NT’s role in maternal defense. Intracerebroventricular (icv) injections of NT significantly impaired defense in terms of time aggressive and number of attacks at all doses tested (0.05, 0.1, 1.0, and 3.0 μg). Other maternal behaviors, including pup retrieval, were unaltered following NT injections (0.05 μg) relative to vehicle, suggesting specificity of NT action on defense. Further, icv injections of the NT receptor 1 (NT1) antagonist, SR 48692 (30 μg), significantly elevated maternal aggression in terms of time aggressive and attack number. To understand where NT may regulate aggression, we examined Fos following injection of either 0.1 μg NT or vehicle. 13 of 26 brain regions examined exhibited significant Fos increases with NT, including regions expressing NT1 and previously implicated in maternal aggression, such as lateral septum, bed nucleus of stria terminalis, paraventricular nucleus, and central amygdala. Together, our results indicate that NT inversely regulates maternal aggression and provide the first direct evidence that lowering of NT signaling can be a mechanism for maternal aggression. To our knowledge, this is the first study to directly link NT to a social behavior.